PERCEPTION OF THE COOPERATIVE UNIT MANAGEMENT AGAINST THE UNDERSTANDING ABOUT THE FINANCIAL REPORT OF THE COOPERATIVE UNIT IN TANGERANG - Hamdani .; Triana Zuhrotun Aulia (The Accounting Journal of Binaniaga, 2018)
This research is to find out the effect of the perception upon the understanding about the financial report of the cooperative unit in Tangerang.  The research has been done at the cooperative units in Tangerang, and the samples of the research is 53 respondents who are the management of the cooperative.  Variables of this research are independent variable which is the perception of the cooperative management (PPK) and dependent variable which is the understanding about the financial report (PALK) Data collection method is field survey using questionnaires, direct interview and library study.  Analysis unit is the people (cooperative unit management). Method of data analysis has applied simple linear regression. Analysis equipment is applying SPSS 24.0. The perception of the cooperative unit management has positively and significantly affected the understanding about the financial report based on SAK, ETAP at the cooperative units in Tangerang. The better perception of the cooperative unit management has improved the understanding of the financial report.Key words:  perception of the management of cooperative unit, understanding about the financial report.